Configurations for positive public behaviors in response to the COVID-19 pandemic: a fuzzy set qualitative comparative analysis - Junwang Gu; Chunmei Wu; Xuanhui Wu; Rong He; Jing Tao; Wenhui Ye; Ping Wu; Ming Hao; Wei Qiu (BMC, 2022)
Abstract Background The COVID-19 crisis poses considerable threats to public health, and exploring the key configuration conditions of the public behavior response is very important for emergency risk management. Objective This study attempts to reveal differences in the conditional configuration and mechanism of public behavior based on the proposed framework, further make up for the deficiencies of existing research in explaining such issues as "How to promote the public's protective behavior or reduce the public's excessive behavior?" and finally provide new evidence and ideas for the government to improve the emergency management system. Methods A total of 735 valid cases were obtained using an online survey and revealed the conditional configuration and mechanism of public behavior differences through a fuzzy set qualitative comparative analysis based on the proposed public behavioral framework. Results The results show that critical factors including risk communication, trust, risk perception, and negative emotions alone did not constitute a necessary condition for public protective or excessive behavior. The different configurations of influencing factors reveal the complexity of public behavioral risk management, and taking adequate measures to increase public trust and reduce negative public emotions constitute the core path of risk management to enhance positive public behavior. Conclusions The configurations of various influencing factors reveal the complexity of public behavioral risk management. For behavioral risk management, governments should focus on adapting to multiple conditions according to their situations and, under the "overall perspective," formulate policies based on local conditions and further form a differentiated risk management path. Practically speaking, for the government, taking adequate measures to increase public trust and reduce negative public emotions is the core path of risk management to enhance positive public behavior.